Development of Prototypes of Exercise Aids (Glow in the dark gate and ball) in an Effort to Increase the Success of Training Programs for Pre-porprov Athletes in Woodball Sports, Klaten Regency - Yulius Agung Saputro; Ayub Tatya Admaja (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2021)
The objectives of the research were to: (1) produce a prototype design of tools in training for beginner and advanced male woodball athletes, (2) test the design of a prototype tool that could be effectively used by athletes to improve skills in training at night, (3) the prototype could used to anticipate training schedule constraints for woodball athletes. The steps used in the development procedure are: (1) Potential and Problems, (2) Develop the initial product, (3) Product Design, (4) Design Validation 2 woodball experts and 2 equipment experts, (4) Design improvement, (5) Product Trial for 6 athletes, and (6) Usage Trial for 10 athletes. The final product is a prototype model of an exercise aid (glow in the dark gate and ball) that can be used for training at night. The results of tool validation from the assessment rubric of woodball experts and equipment experts can answer complaints about the tight schedule of activities for athletes, while the effectiveness of the tool model can help coaches in maximizing training programs with experimental assessments by woodball experts on small-scale trials and large-scale trials getting an average score average after doing the test.